Evaluate the Effectiveness of Sterilization Process Educational Program on Operating Room Nurses Knowledge at Al- Hilla City - Al-Hamza, Nada Ali Abed; Ali, Sahar A.; Hamza, Heba Jassim (International Journal of Psychosocial Rehabilitation, 2020)
Background: Sterile technique becomes a foundation of modern surgical procedure and thus rigid adherence to a prescribed sterile technique procedure is essential for the patient's protection as well as for operating room complicated staff.Objective: To evaluate the effectiveness of sterilization educational programs on the operating room nurse's knowledge.Methodology: Quasi-experimental design selected to carried out this quantitative study to evaluate the effectiveness of sterilization process educational program on operating room nurses knowledge. Non- probability purposive sample choose which consist of (55) operating room nurses. The validity of the program and the prepared questionnaire was assessed by expert panel, Correlation coefficient method used, to calculate the reliability which recorded about (0.81) which is statistically accepted.Results: tabulated data shows that most of the study sample among two groups were with (24- 27) years age group, 20(66%) and 15(60%) were female, while bachelor holder appear as a dominant education level for the participant 21(70%) for control group and 14(56%) for the interventional group. Both groups recorded low responses related to their knowledge about sterilization in during pre- test.Conclusion: the educational program which directed to sterilization process act as an effective factor on the operating roomRecommendation: to enhance quality of care which provided to the patients who operating room nurses to improve their knowledge and update their information related to sterilization process.